Analysis of Success Values with Internalization of IQ, SQ, and EQ in Achievement’s Students in Zone Course Institution - Nuryana, Amiatun; Mardianti, Linda (Universitas Muhammadiyah Gorontalo, 2024)
Abstract This study aims to identify the influences and analysis of success with the internalization of emotional intelligence, intellectual intelligence, and spiritual intelligence in achievement on the learning outcomes of students in Zone Course Institution. The data was analysis quantitative also deviation standard and qualitatively. The result informed that the students' emotional intelligence has so much effect on the students' character and the contribution to the environment and the learning outcomes. The capability of the student that has balanced intellectual intelligence, spiritual intelligence, and emotional intelligence has a worthwhile contribution because they are able to manage emotion, ability to perceive, interpret, demonstrate, and relate effectively and constructively with other people. The ability to express and control emotion is very important, as is the ability to understand and respond to the emotions of others. Hopefully, all students can meet high criteria in understanding IQ, SQ, and EQ to achieve good goals in the future.Keywords: Emotional Intelligence, Intellectual Intelligence, Spiritual Intelligence